Improving Reading Comprehension Skill of Civil Engineering Students through Collaborative Strategy - Addy Utomo (Ma Chung Press, 2019)
This paper centers around the application of the collaborative strategy on first semester student of the Civil Engineering Department of ITN Malang who have problems in English. The use of collaborative strategic reading (CSR) was to help the students to improve their reading comprehension skill. This research was conducted (1) to know the response of the first semester student of civil engineering ITN Malang after using CSR method to improve their reading skill, and (2) to know the effect of CSR method towards their reading. CSR is a research-based instructional practice in teaching reading comprehension to enhance content area learning. It is the best way to teach reading comprehension with four strategies of CSR because students can learn in groups. Model of classroom action research developed by Kemmis &Mc Taggart (1999) was applied. Preceed with intial recoinnaisance step held before four steps of teaching (planning, implementing, observing, and reflecting) this research was conducted in two cycles, the first cycle to implement strategy add by reading comprehension test and second cycle to implement strategy. The data research obtained through observation and field notes during teaching-learning processes ended with reading tests. The finding showed that collaborative strategic reading improved students` reading comprehension skill.